ChatGPT and its impact on research supervision: Insights from Australian postgraduate research students - Dai, Yun; Lai, Sichen; Lim, Cher Ping; Liu, Ang (Australasian Journal of Educational Technology, 2023)
As artificial intelligence (AI) continues to evolve, its impact on academic environments, especially in postgraduate research supervision, becomes increasingly significant. This study explored the impact of ChatGPT, an advanced AI conversational model, on five dimensions of research supervision: functional, enculturation, critical thinking, emancipation and relationship development. Using a qualitative approach, we examined the practices and perspectives of 20 postgraduate research students with at least 4 months’ experience of using ChatGPT in research activities in Australia. The study revealed several areas of impact, including accelerated research progress, enhanced research quality, improved scholarly development and professional skills, enhanced critical thinking, increased student confidence and autonomy, and a deeper supervisory relationship. The findings suggest a shift in the roles and responsibilities of supervisors and students: the former provides strategic direction and high-level guidance, while the latter transits from apprentices to autonomous researchers due to the independence fostered by ChatGPT. This shift suggests an evolving model of postgraduate research supervision, with educational technology acting as epistemic tools to enhance the supervisory process. The study also considers the ethical implications of AI-enabled support. Implications for practice or policy: Postgraduate students can be facilitated by ChatGPT in self-directed research for enhanced independence and autonomy. Supervisors can deploy supervisory meetings for high-level guidance and personalized feedback in an AI-enhanced supervision model. Postgraduate programmes can leverage generative AI tools for an AI-enhanced research supervision model. Universities need to develop AI literacy curricula and protocols to guide students towards responsible use of generative AI tools while addressing potential challenges.